Analysis of leaky-wave antenna based on partially-filled rectangular waveguide - R. R. Abdullin; S. N. Shabunin (Известия высших учебных заведений России: Радиоэлектроника, 2015)
A leaky-wave antenna based on the partially-filled rectangular waveguide with transverse slots is investigated. Using tensor Green’s functions for antenna radiation analysis is suggested. A transcendental equation for a complex wavenumber obtained by matching magnetic fields inside and outside the waveguide is presented. Plots of velocity factor dependencies on waveguide filling parameters are shown. An influence of dielectric layer position on the antenna performances is investigated. Radiation pattern is estimated.